The Wiley-Blackwell Handbook of The Treatment of Childhood and Adolescent Anxiety - Essau, Cecilia A. (Wiley, 2012)
Wiley-Blackwell Handbook of the Treatment of Childhood and Adolescent Anxiety presents a collection of readings from leading experts that reveal the most effective evidence-based interventions for the prevention and treatment of anxiety disorders in children and adolescents. Features expertise of the foremost scientist-practitioners in the field of child and adolescent anxiety Includes state-of-the art information on psychological interventions from each author Written in a clear and easy-to-follow manner for a wide audience